Financial Report Analysis to Assess Financial Performance at PT. Astra International Tbk for the 2019 – 2022 Period - Sitorus, Fungky Yohanes; Br Purba, Rahima (Formosa Journal of Sustainable Research, 2024)
The purpose of this study, "Financial Statement Analysis to Assess the Financial Performance of PT. Astra International Tbk for the Period 2019 - 2022," is to use quantitative descriptive methodologies to assess PT Astra International Tbk's financial performance during the previous four years. With secondary data from financial accounts, this technique offers a methodical summary of the company's liquidity, solvency, activity, and profitability. As PT Astra International Tbk has demonstrated strength in controlling its long-term liabilities, the study's results show that the company has a very good solvency ratio over the timeframe. The state of asset management, operational efficiency, and profit generation is subpar, as seen by the notable obstacles to activity, profitability, and liquidity.